Farmers knowledge on pesticide management practices: A case study of shallot growers in Palu, Indonesia. Issue 2 (July 2021) - Jaya, K; Ratnawati, R; Asman, A; Arfan, A
Abstract: Pesticide is one of the most common methods of pests and diseases control applied in a developing country. Knowledge of pesticide management is significant for effective application. The purpose of the study is to determine the knowledge of farmers about pesticide management practices on shallot crops in Palu, Central Sulawesi, Indonesia. The study was conducted from October 2017 to February 2018. This quantitative and survey research was used respondents of 30 farmers in two locations: Duyu and Bayaoge in Tatanga District, Palu, Central Sulawesi, Indonesia. Commonly, the respondents working on the shallot field. The data quantification using the ordinal scale, then univariate analysis for frequency distribution and bivariate analysis to determine the correlation of two variables. The results were showed there no significant effect between farmers' knowledge about pesticides and the actions of farmers in the use of pesticides. Increasing knowledge about pesticides cannot be expected to change wise actions in using pesticides in pest control.